2015
DOI: 10.1165/rcmb.2013-0489oc
|View full text |Cite
|
Sign up to set email alerts
|

SH2 Domain-Containing Protein Tyrosine Phosphatase 2 and Focal Adhesion Kinase Protein Interactions Regulate Pulmonary Endothelium Barrier Function

Abstract: Enhanced protein tyrosine phosphorylation is associated with changes in vascular permeability through formation and dissolution of adherens junctions and regulation of stress fiber formation. Inhibition of the protein tyrosine phosphorylase SH2 domaincontaining protein tyrosine phosphatase 2 (SHP2) increases tyrosine phosphorylation of vascular endothelial cadherin and b-catenin, resulting in disruption of the endothelial monolayer and edema formation in the pulmonary endothelium. Vascular permeability is a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Cationic liposomes encapsulating cDNA encoding Rab4 wt , Rab4 Q67L , Rab4 S22N , or GFP were injected into the retro-orbital vein of C57/BL6 mice. Previous studies with cationic liposomes demonstrate that overexpression is observed at 48 hours after injection of cDNA for proteins of varying molecular weight from 27 to 78 kD; however, it is likely that protein overexpression occurs throughout the lung, and not specifically in endothelial cells (11,21,23,24). At 44 hours after liposome injection, mice were exposed to the live bacteria, P. aeruginosa strain PA103, via intratracheal injection, for a further 4 hours and pulmonary edema formation was assessed by lung wet-to-dry ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic liposomes encapsulating cDNA encoding Rab4 wt , Rab4 Q67L , Rab4 S22N , or GFP were injected into the retro-orbital vein of C57/BL6 mice. Previous studies with cationic liposomes demonstrate that overexpression is observed at 48 hours after injection of cDNA for proteins of varying molecular weight from 27 to 78 kD; however, it is likely that protein overexpression occurs throughout the lung, and not specifically in endothelial cells (11,21,23,24). At 44 hours after liposome injection, mice were exposed to the live bacteria, P. aeruginosa strain PA103, via intratracheal injection, for a further 4 hours and pulmonary edema formation was assessed by lung wet-to-dry ratio.…”
Section: Discussionmentioning
confidence: 99%
“…SHP2 inhibition reduced basal monolayer resistance in PAECs and promoted an increase in phosphorylated VE-cadherin and β -catenin as measured by IP and phosphotyrosine Western blot [ 142 ]. More recently, it was shown that both LPS and thrombin treatment induced a reduction in lung SHP2 activity and association with FAK [ 187 ]. Further, liposomal delivery of a constitutively active (D61A) SHP2 mutant reduced pulmonary edema in mice challenged with LPS or Pseudomonas aeruginosa [ 187 ], suggesting that SHP2 plays an important role in preventing acute lung injury.…”
Section: The Other Side Of the Coin: Tyrosine Phosphatasesmentioning
confidence: 99%
“…Liposomes were prepared as described elsewhere (36,37). In brief, dimethyldioctadecylammonium bromide and cholesterol were mixed in chloroform, then chloroform was evaporated by using a rotary evaporator under vacuum at 37°C until a thin lipid film formed.…”
Section: Liposome Preparationmentioning
confidence: 99%